Acute Physiological and Psychological Stress Response in Youth at Clinical High-Risk for Psychosis - Carol, Emily E.; Spencer, Robert L.; Mittal, Vijay A. (Frontiers in Psychiatry, 2021)
Deficits in stress-response systems are a characteristic of schizophrenia and psychosis spectrum illnesses, and recent evidence suggests that this impairment may be evident in those at clinical high-risk (CHR) for the development of a psychotic disorder. However, there is limited research specifically investigating biological and subjective stress reactivity in CHR individuals. In the present study, 38 CHR individuals and group of 38 control individuals participated in the Trier Social Stress Test (TSST), an experimentally induced psychosocial stressor. Changes in salivary cortisol and alpha amylase, as well as self-reported units of distress (SUDS), were evaluated. Interestingly, the TSST did not induce a change in cortisol levels in either group, though the CHR group did show higher overall cortisol levels throughout the TSST (pre-anticipation period through recovery period). However, indicative of an effective task manipulation, the TSST did illicit an increase in alpha amylase in both groups. CHR participants exhibited higher levels of subjective stress prior to the stressor compared to the control group and CHR SUDs did not significantly increase in response to the stressor. In contrast, the control group showed an increase in SUDS in response to the stressor. Notably, SUDS for the control group post task mirrored the levels CHR youth endorsed prior to the stressor. Taken together, these findings suggest that there may be a functional relationship between persistently elevated cortisol and chronic high levels of subjective distress in CHR individuals.